Advantages of the non-irrigated catheters use in atrial fibrillation catheter ablation - A. Doronin; J. Suslina; V. Khanenova; M. Meshkova (Ukrainian Journal of Cardiovascular Surgery, 2016)
In this article we analyzed our own experience of the atrial fibrillation (AF) catheter treatment without the use of irrigated catheters and navigation systems. The study group included 100 consecutive patients, who in the period from May 2013 to July 2015 in Ukrainian Children’s Cardiac Center underwent primary catheter ablation of atrial fibrillation. Paroxysmal AF was observed in 45 (45.0%) patients, persistent – in 33 (33.0%), long-standing persistent – in 22 (22.0%) patients. There were 2 complications: 1 pericardial tamponade and 1 pseudoaneurysm of the femoral artery. During the 1 year of follow up without the use of antiarrhythmic drugs in sinus rhythm were 67 (67.0%) patients.